Intra-cardiac motion detection catheter for the early identification of acute pericardial tamponade during invasive cardiac procedures - Selvakumar, Dinesh; Barry, Michael A.; Pouliopoulos, Jim; Lu, Juntang; Tran, Vu; Kovoor, Pramesh (Frontiers in Cardiovascular Medicine, 2024)
To develop and test an intra-cardiac catheter fitted with accelerometers to detect acute pericardial effusion prior to the onset of hemodynamic compromise.Early detection of an evolving pericardial effusion is critical in ensuring timely treatment. We hypothesized that the reduction in movement of the lateral heart border present in developing pericardial effusions could be quantified by positioning an accelerometer in a lateral cardiac structure.A 'motion detection' catheter was created by implanting a 3-axis accelerometer at the distal tip of a cardiac catheter. The pericardial space of 5 adult sheep was percutaneously accessed, and pericardial tamponade was created by infusion of normal saline. The motion detection catheter was positioned in the coronary sinus. Intracardiac echocardiography was used to confirm successful creation of pericardial effusion and hemodynamic parameters were collected.Statistically significant reduction in acceleration from baseline was detected after infusion of only 40mL of normal saline (p<0.05, ANOVA). In comparison, clinically significant change in systolic blood pressure (defined as >10% drop in baseline systolic blood pressure) occurred after infusion of 80mL of normal saline (107 ± 22 mmHg vs. 90 ± 12 mmHg p=0.97, ANOVA), and statistically significant change was recorded only after infusion of 200mL (107 ± 22 mmHg vs. 64 ± 5 mmHg, p<0.05, ANOVA).An intra-cardiac motion detection catheter is highly sensitive in identifying acute cardiac tamponade prior to clinically and statistically significant changes in systolic blood pressure, allowing for early detection and treatment of this potentially life-threatening complication of all modern percutaneous cardiac interventions.